Evaluation of disinfection efficiency in pet's hospital by using chlorine dioxide - Ching-Shan Hsu (Sustainable Environment Research, 2016)
Microbial aerosols could cause various human and animal health problems and their control is becoming a significant scientific and technological topic for consideration. The main objectives of this study were to monitor bioaerosol levels of the pet's hospital and then to perform disinfection efficiency by applying chlorine dioxide. The air quality within these pet's hospitals should satisfy the guidelines specified by the Taiwan Environmental Protection Administration (TEPA). Accordingly, this study performed an experimental investigation into the efficiency of two different gaseous chlorine dioxide (0.3 mg m−3) treatments in disinfecting a local pet's hospital, namely a single, one-off application and a multiple-daily application. In both cases, the ClO2 was applied using strategically-placed aerosol devices. The air quality before and after disinfection was evaluated by measuring the bioaerosol levels of bacteria and fungi. The experimental results found that the average background levels of bacteria and fungi prior to ClO2 disinfection were found to be 2014 ± 1350 and 1002 ± 669 CFU m−3, respectively. A single ClO2 application was found to total disinfected bacteria and fungi concentration levels by as much as 57.3 and 57.6%. By contrast, a multiple-daily ClO2 application was found to total disinfected bacteria and fungi concentration levels by as much as 65.1 and 57.6%. Among the two disinfection methods, the multiple-daily ClO2 application method was found to yield a higher disinfection efficiency for bacteria, i.e., 16.28 ± 0.92%. Thus, using a ClO2 disinfectant to maintain the air quality is of great importance to reduce infectious diseases in the pet's hospital. Therefore, the results suggest that the air quality guidelines prescribed by the TEPA for pet's hospital and other animal facilities can best be achieved by applying chlorine dioxide at regular intervals. The ClO2 aerosol devices can effectively restrain or disinfect airborne bacteria to improve the indoor air quality. Thus, it can be applied in pet's cosmetology institutions, hospitals, and other public areas, where bioaerosols are of great concern.